Autocuidado de personas con diabetes mellitus de tipo 2 en tiempos de pandemia por Sars-CoV-2 (Covid-19): Medida para la prevención de contagio - Ureta Jurado, Raúl (2023)
Self-care activities are learned as the mature individual, and are affected by cultural beliefs, habits, customs of the family and society. Effective practice of self-care plays an important role in keeping diabetes mellitus under control, both in prevention and during the disease. The objective of the study was to determine the self-care measures of patients with type 2 diabetes mellitus at the Regional Hospital of Huancavelica. Methods: a quantitative study was carried out, Descriptive level, with Non-experimental, Transectional, Descriptive design. The sample includes patients with type 2 diabetes mellitus (n = 60). For data collection, the survey technique was applied with the questionnaire instrument. The instrument developed by Amaya in 2017 was applied, which has a validity and reliability of 0.86% on self-care measures consisting of 20 questions. Applying by phone. Results: 65.0% of surveyed patients present inadequate self-care measures; and only 35.0% present adequate self-care measures. 51.7% present adequate self-care in physical exercise, 88.3% present inadequate self-care in eating, and 88.3% present inadequate self-care in the assessment of the feet. And 60.0% present inadequate self-care in pharmacological treatment. Conclusions: The self-care measures of patients with type 2 diabetes mellitus are mostly inadequate in the dimensions of Food, Foot care and pharmacological treatment, therefore it is necessary to implement health strategies within the framework of health promotion for strengthening self-care measures and can prevent complications of the disease.